Lesser Himalayan Tertiary rocks in west Nepal and their extension in Kumaun, India - Dhital, Megh Raj (Journal of Nepal Geological Society, 2012)
In the inner Lesser Himalaya of west Nepal, the Tertiary rocks belonging mainly to Eocene–Miocene age are made up of redpurple, brown, and grey-green sandstones and shales with sporadic lenticular limestone beds of the Chuchura Formation containing Nummulites and bivalvia fossils. Similar sequences exist in the adjoining border region of the Kumaun Lesser Himalaya, India, where these rocks are assigned a Precambrian age and belong to the Rautgara Formation at its type locality near Pancheshwar. A detailed study of lithofacies and sedimentary structures in the Kumaun Lesser Himalaya, especially at Rautgara, in the Hewal Nadi, around Nilkanth, on the Rishikesh–Badrinath Road, in the vicinity of Khadi, between Chham and Dharasu, and south of Chakrata revealed that the rocks are made up mainly of fining-upwards fluvial cycles underlain by shallow marine deposits. The rocks exposed in a tectonic window between Saknidhar and Deoprayag exhibit mainly fluvial deposits with large-scale cross-beds. A few coal seams encountered north of Chham and some bivalvia and Turitella fossils recovered at Bachhelikhal (16.0 km south of Deoprayag, on the Rishikesh–Badrinath Road) allow assigning the succession to the Lesser Himalayan Tertiary. Jour. Nep. Geol. Soc., Vol. 37, 2008, 11-24